Auger electron spectroscopy of boron nitride whiskers produced in optical furnace without catalysts - Sartinska, L.L.; Stonis, V.V.; Frolov, A.A. (Современные проблемы физического материаловедения, 2009)
Results of Auger electron spectroscopy (AES) investigations of boron nitride whiskers produced in optical furnace without catalysts as well boron and initial h-BN for comparison are presented. The Auger process was initiated by exposing the sample to a beam of high energy electrons 3 keV.